Targeting the Spleen as an Alternative Site for Hematopoiesis. (10th April 2019) - Short, Christie; Lim, Hong K.; Tan, Jonathan; O'Neill, Helen C.
Abstract : Bone marrow is the main site for hematopoiesis in adults. It acts as a niche for hematopoietic stem cells (HSCs) and contains non‐hematopoietic cells that contribute to stem cell dormancy, quiescence, self‐renewal, and differentiation. HSC also exist in resting spleen of several species, although their contribution to hematopoiesis under steady‐state conditions is unknown. The spleen can however undergo extramedullary hematopoiesis (EMH) triggered by physiological stress or disease. With the loss of bone marrow niches in aging and disease, the spleen as an alternative tissue site for hematopoiesis is an important consideration for future therapy, particularly during HSC transplantation. In terms of harnessing the spleen as a site for hematopoiesis, here the remarkable regenerative capacity of the spleen is considered with a view to forming additional or ectopic spleen tissue through cell engraftment. Studies in mice indicate the potential for such grafts to support the influx of hematopoietic cells leading to the development of normal spleen architecture. An important goal will be the formation of functional ectopic spleen tissue as an aid to hematopoietic recovery following clinical treatments that impact bone marrow. For example, expansion or replacement of niches could be considered where myeloablation ahead of HSC transplantation compromises treatment outcomes. Abstract : Harnessing the spleen in early recovery from myeloablation associated with hematopoietic stem cell (HSC) transplantation through 1) infusion of stromal cells for repair of HSC niches and formation of ectopic niches, 2) directing HSC into spleen for early hematopoiesis, and 3) infusion of multipotent progenitors (MPPs) for early myelopoiesis leading to 4) production of monocytes for early immune recovery.